PENGARUH PENGGUNAAN HIDROKSI PROPIL METIL SELULOSA (HPMC) SEBAGAI GELLING AGENT TERHADAP SIFAT FISIK MASKER PEEL OFF EKSTRAK DAUN SIRIH (Piper betle L.) - Nurul Istiqomah; Metha Anung Anindhita (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2018)
Peel off mask are cosmetic that use for facial skincare. Piper betle L. leaf has the properties to kill Staphylococcus epidermidis bacteria that cause acne. Peel off mask is a gel drug delivery system which requires gelling agent material. HPMC is one of the gelling agent that preferred properties. This study aims to examine the physical properties of Piper betle L. leaf peel off mask with HPMC as g gelling agent. The active substance used is Piper betle L. leaf extract that using maseration method. To determine the effect of using HPMC variation on physical properties it is carried out by organoleptic testing, viscosity, adhesion, dispersion, homogeneity, pH and irritation. The result of this study showed that the variation of HPMC had effect on organoleptic, viscosity, adhesion, dispersion and rate of drying and has no effect on homogeneity, pH, and irritation. Keyword : Piper beatle leaf, peel off mask, HPMC